FUNGSI SIDIK JARI DALAM PENGUNGKAPAN TINDAK PIDANA PENCURIAN DI RESKRIM POLRESTA PADANG - Riki Mardona dan Nurlinda Yenti (Fakultas Hukum Universitas Tamansiswa Padang, 2019)
Every criminal act must contain an element of unlawfulness and the act is threatened with criminal action. Whereas to be able to determine a crime can proceed to the investigation stage, preliminary evidence or sufficient evidence must be available, one of which is fingerprint evidence. The existence of a fingerprint is one of the most important elements in the identification process to reveal the crime units of the Criminal Police Criminal Unit in Padang . From the results of the study it was found that the existence of fingerprints is very supportive as one of the evidences in the disclosure of criminal acts of theft in the investigation process by the Padang Police Criminal Investigation. The obstacle is that there is still limited equipment for identification, as well as if the equipment is experiencing technical damage that there is only 1 (one), so that a simple method of attachment is used through special ink paper and using powder, as well as supporting facilities and infrastructure as well as human resources which exists. While the effort to overcome these obstacles is to maximize the existing equipment, as well as efforts to increase the ability of personnel in the use of fingerprint identification tools through training held by the Indonesian Police Headquarters in Jakarta.